Audiovisual resources in the media and their role in teaching Law - López-Oliva, José; Alarcón-Peña, Andrea; Vargas-Chaves, Iván (Law, State and Telecommunications Review, 2025)
[Purpose] The primary objective of this research is to explore and demonstrate the efficacy of audiovisual resources as a pedagogical tool in the teaching of Law, particularly in areas such as civil and state liability, and evidentiary and procedural rights. [Methodology] A qualitative approach with a correlational scope was employed to gain a deep understanding of the meanings and relationships between variables. This included content analysis to identify relevant legal themes and how they were represented, as well as analogies to compare and contrast different interpretations of audiovisual content. This research seeks to demonstrate that audiovisual resources can be a valuable tool for teaching Law by allowing for a more dynamic, critical, and relevant approach to legal content. [Findings] The results of this research reveal the transformative potential of audiovisual materials in legal education. By integrating films and television series into teaching processes, a significant renewal in pedagogical methods was observed, making the subject more attractive and relevant to students. Additionally, the analysis of these fictional representations allowed for a deeper connection between theoretical knowledge and social reality, fostering more meaningful learning.